GCC Banking Companies Risk Management Practices and its Impact on Their Financial Performance - Alali, Hussain (2023)
This article aims to explore the risk management practices (RMPs) of Islamic banks (IBs) and conventional banks (CBs) in the Gulf Cooperation Council (GCC). It assesses the different phases of RMP, including risk understanding; risk identification; risk assessment and analysis; and risk monitoring. This study conducts a structured survey questionnaire to assess the RMP in both types of banks. We find that both types of banks rank the importance of RMP above the mid-point of the 5-point Likert scale. Using t-test analysis, we find no significant difference in RMP between both types of banks, except for understanding risk practice phase. Managers of CBs have a better understanding of risk management (RM) than IBs. We also examine the impact of RMP on banks’ financial performance. The average return on Assets (ROA) and the average return on equity (ROE) over the years (2010–2017) are used as a proxy for financial performance. Applying robust White regression OLS, we find a significant impact on financial performance measures only for IBs. We refer to the fact that IBs follow the equity approach based on risk-sharing with their clients (depositors and investors). The regulatory authorities may find this study useful in enticing banks to implement the best RMP and so improve banks’ performance.